(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The paper analyses a case of overtreatment practiced by certain physicians on a child few months old suffering from a very serious syndrome that left no life expectancy, against the will of his parents. The case went before the Court of Bari that has recently ruled in favour of the child’s parents and recognized their right, iure proprio and iure hereditatis, to compensation for the biological damages suffered. The author discusses the peculiarities of the doctor-patient relationship when the patient is a neonate and why in these cases the concept of overtreatment is especially important for the protection of the patient’s rights. The author then moves from the specific case to analyse in broader terms the difficulties still existing in defining what objectively is “overtreatment”.